2010
DOI: 10.1162/neco_a_00006-arleo
|View full text |Cite
|
Sign up to set email alerts
|

How Synaptic Release Probability Shapes Neuronal Transmission: Information-Theoretic Analysis in a Cerebellar Granule Cell

Abstract: A nerve cell receives multiple inputs from upstream neurons by way of its synapses. Neuron processing functions are thus influenced by changes in the biophysical properties of the synapse, such as long-term potentiation (LTP) or depression (LTD). This observation has opened new perspectives on the biophysical basis of learning and memory, but its quantitative impact on the information transmission of a neuron remains partially elucidated. One major obstacle is the high dimensionality of the neuronal input-outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 83 publications
5
64
0
Order By: Relevance
“…We modeled stochastic pre-synaptic release of the excitatory and inhibitory phasic components (i.e., the α 1 receptor). The stochastic quantal release model was implemented as in Arleo et al (2010) by splitting each synapse into a fixed number of independent releasing sites (RS) and independent post synaptic densities (PSD). The presynaptic RSs and the postsynaptic PSDs were endowed with the same kinetic scheme as in the deterministic model.…”
Section: Methodsmentioning
confidence: 99%
“…We modeled stochastic pre-synaptic release of the excitatory and inhibitory phasic components (i.e., the α 1 receptor). The stochastic quantal release model was implemented as in Arleo et al (2010) by splitting each synapse into a fixed number of independent releasing sites (RS) and independent post synaptic densities (PSD). The presynaptic RSs and the postsynaptic PSDs were endowed with the same kinetic scheme as in the deterministic model.…”
Section: Methodsmentioning
confidence: 99%
“…Synaptic vesicle release has only recently been studied in a probabilistic or information-theoretic manner (3)(4)(5). A systematic perspective on how stochastic vesicle release affects neural code processing at synapses is still lacking.…”
mentioning
confidence: 99%
“…31.6) has revealed that the whole set of complex properties of intrinsic excitability and synaptic transmission can be reproduced by appropriate mechanisms derived from experimental observations. These models allowed an explanation of properties like resonance Nieus et al 2006) and synaptic plasticity (Nieus et al 2006), Na + channel localization and spike generation (Diwakar et al 2009), stochastic release, and mutual information (MI) transfer (Arleo et al 2010). The granule cell models, together with those of the Golgi cell, are currently being used to generate new network models reproducing all known granular layer spatiotemporal dynamics ) and reconnecting molecular and cellular properties of the granule cell to global network computations.…”
Section: Granule Cell Modelsmentioning
confidence: 99%
“…Recently, a computational model has shown that at least half of the information passing through the mossy fiber-granule cell relay is conveyed by first spike delay (Arleo et al 2010). New experiments and computational models are required to fully understand the functional role of the granule cells.…”
Section: New Views On the Granule Cell Function: Transformations Of Smentioning
confidence: 99%